Simulation Analysis and the Improvement of the Omnibearing Walking Robot - Liang Hu; Luo Qiang; Deng Zhenghua; Ge Weiguo (Jixie chuandong)
A robot which redesigned based on the omnibearing level posture robot is introduced. By adding a rotating mechanism on each sole,the redesigned robot can walk on the slope surface,thereby,it can walk on the two special surfaces as horizontal surface,slope surface,and overcome the vertical surface. The modeling of robot is carried out,and calculate the stroke relations among all the legs,the location relations between the robot and the environment,and the gradeability of the robot and so on are analyzed. The simulation analysis of two kinds of contact way and force condition of the key parts while it walks from horizontal surface to slope surface are analyzed by using Solidworks and ADAMS software.